Tygrys: gnoza polityczna - Małgorzata Zemła (Postscriptum Polonistyczne)
The article is dedicated to Czesław Miłosz's essay Tiger, analysing the heterodox discourses that it contains, especially the political gnosis. The author analyses the connections between such discourses and the notions of deep crisis of European culture, showing also how Miłosz solved the dialectic argument with his friend Tadeusz Juliusz Kroński, a Hegelian philosopher. Miłosz's solution enabled him to give up both Gnostic catastrophism and a temptation of hermetic utopia by Kroński. Towards the end of the essay the history of mankind regains its value and it is being reintegrated as a history of Salvation.